The Company Practice Strategy In Developing Work Relationships With Employees At PT. Bakrie North Sumatra Plantations Asahan District - Nurul Putri Tantina; Muhammad Alfikri (LEGAL BRIEF, 2022)
The purpose of this research is to determine the effectiveness of the company's public relations strategy in fostering working relationships with employees at PT. Bakrie Sumatera Utara Plantations in Asahan Regency. In this study, the author employs Thomas L. Harris's theory of communication strategy from his book Crisis Public Relations, which proposes that public relations strategies include publications, events, news and information or image, lobbying and negotiations, and social responsibility. The descriptive qualitative research method was used. The findings revealed that PT. Bakrie Sumatera Utara Plantations' Public Relations had implemented communication strategies such as communicating and accommodating all employee complaints and appealing to all employees to help each other, holding entertainment, awards, and social events, and collaborating with both electronic and print media as media. a location for developing positive relationships with both internal and external parties